Phenolic constituents from the stem barks of Rhizophora apiculata Blume - Binh, Pham Thanh; Chien, Nguyen Van; Trung, Nguyen Quoc; Thong, Vu Huy; Tuyen, Nguyen Van; Thao, Nguyen Phuong (Vietnam Journal of Science and Technology, 2020)
Using various chromatographic separations, seven phenolic derivatives (1‒7) were isolated from a methanolic extract of R. apiculata stem barks. Their structures were elucidated to be dunnianoside E (1), (+)-dihydroquercetin (2), 2,6-dimethoxy-[1,4]benzoquinone (3), 2,4,6-trimethoxyphenol (4), 3,4,5-trimethoxybenzyl alcohol (5), hydroxytyrosol (6), and methyl 3,4-dihydroxycinnamate (7) by detailed analysis via spectroscopic techniques (1D, 2D NMR and ESI-MS data) as well as comparison with those reported. This is the first report of compounds 1 and 4‒7 from Rhizophora genus.